Ethanol-induced cardiomyocyte toxicity implicit autophagy and NFkB transcription factor. (July 2018) - Maiuolo, Jessica; Maretta, Alessia; Gliozzi, Micaela; Musolino, Vincenzo; Carresi, Cristina; Bosco, Francesca; Mollace, Rocco; Scarano, Federica; Palma, Ernesto; Scicchitano, Miriam; Nucera, Saverio; Sergi, Domenico; et al.
Graphical abstract: Abstract: Chronic ethanol (EtOH) consumption causes early detrimental consequences in many tissues including the myocardium, though the molecular mechanisms leading to the alcoholic cardiomyopathy (ACM) still remain to be elucidated. Here, we studied several biomolecular changes occurring in cardiomyoblasts after their exposure to sublethal concentrations of EtOH and the potential synergistic effect with methylmercury (MM) or doxorubicin (DOXO), which are known to produce direct myocardial dysfunction. In addition, the possible role of autophagic responses and Nuclear Factor kappa-B (NFkB) modulation in early post-alcoholic myocardial damage has been investigated. H9c2 rat cardiomyoblasts were incubated for fifteen days with a sub-lethal concentrations of EtOH (1–1000 μM). In particular, treatment of H9c2 cells with EtOH produced an increase of reactive oxygen species (ROS) and the activation of autophagy. Furthermore, chronic exposure to EtOH, was accompanied by a translocation of NFkB into the nucleus dose-dependently. Finally, co-incubation of EtOH (1–1000 μM) with sublethal concentrations of MM or DOXO showed a prominent apoptotic death of cardiomyoblasts accompanied by ROS overproduction, autophagy activation and by an increased nuclear translocation of NFkB as compared to untreated cells. Thus, EtOH produces early changes in cardiomyoblasts characterized by oxidative stress, reactive autophagy and NFkB modulation at concentrations unable to produce direct cell death. Combination of EtOH with cardiotoxic pollutants or drugs makes the cardiomyocyte vulnerable to exogenous insults leading to apoptosis. These data contribute to better identify molecular mechanisms underlying early stages of alcoholic cardiomyopathy and suggest novel strategies to counteract integrated risk of cardiotoxicity in chronic alcohol consumption.